2017
DOI: 10.12659/msm.902106
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Oxidative Stress and Peripheral Leukocyte Telomere Length in Patients with Premature Coronary Artery Disease

Abstract: BackgroundLeukocyte telomere length (LTL) is regarded as a potential marker of biological aging. Oxidative stress plays a major role in the rate of telomeric DNA loss. The aim of this study was to explore whether the LTL was shorter in Chinese patients with premature coronary artery disease (PCAD) than in non-CAD controls and to determine the relationship between oxidative stress and LTL shortening in this population.Material/MethodsPatients for coronary angiography were recruited. In total, 128 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Previous studies showed there were cases of shortening of telomere length in patients with CHD in both Caucasians [26, 27] and Asians [28, 29]. A study examined the LTL by 1525 postmenopausal women and indicated that LTL was closely related to human race.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed there were cases of shortening of telomere length in patients with CHD in both Caucasians [26, 27] and Asians [28, 29]. A study examined the LTL by 1525 postmenopausal women and indicated that LTL was closely related to human race.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous findings support that oxidative stress is related to telomere shortening [25]. Oxidative stress triggers telomere attrition in endothelial cells [26] and vascular smooth muscle cells [27,28].…”
Section: Discussionmentioning
confidence: 93%
“…People with cardiovascular diseases are also characterized by shortening of telomeres and an increased level of oxidative stress (Tian et al, 2017). These regularities seem to be less pronounced in those who practice an active lifestyle.…”
Section: Discussionmentioning
confidence: 99%